Penerapan Metode Certainty Factor dalam Sistem Pakar Pendeteksi Resiko Osteoporosis dan Osteoarthritis - Stephanie Halim; Seng Hansun (Ultima Computing : Jurnal Sistem Komputer, 2015)
Osteoporosis is commonly referred to “thinning” and osteoarthritis referred to “calcification”, but people giving wrong action treatment of these two diseases. Therefore, the aim of this study is to develop an android-based application to identify the risk of osteoporosis and osteoarthritis. To identify that risk was processed using certainty factor method. Certainty factor method related about event based on facts, which the source of those facts are from expert and assumed with a value, called certainty factor. From the testing result, the accuracy of this expert system is about 80%. Index Terms - Certainty factor, disease diagnose, expert system, osteoarthritis, osteoporosis